Foaming-based wearable single-layer friction nano-generator and preparation method and application thereof
Through the composite of thermoplastic elastomer and conductive carbon material and supercritical CO2 foaming treatment, the problem of fewer cases of combining nano-trigger generators with supercritical foaming and difficult to match the strength and stiffness of the material is solved, and a nano-trigger generator with high dielectric and conductive properties is realized, which is suitable for wearable devices.
Patent Information
- Application Number
- CN202411745834.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, there are few cases of nano-trigger generators combined with supercritical foaming, and traditional nano-power generation mechanisms increase the production process complexity and difficulty in assembling dielectric and conductive layers. The fibrillation of engineering plastics increases the strength and stiffness of the material, making it difficult to use in wearable materials.
The thermoplastic elastomer is combined with a conductive carbon material, and the foam-based wearable single-layer friction nanogenerator is formed through supercritical CO2 foaming treatment. The dielectric layer and the conductive layer are integrated into one, simplifying the structure.
It improves the dielectric and conductivity of nano friction generators, significantly improves output performance, simplifies the structure, is suitable for wearable devices, and improves the flexibility and mechanical properties of the material.
Smart Images

Figure CN119765979A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer microporous foaming, and in particular to a foam-based wearable single-layer friction nanogenerator and a preparation method and application thereof. Background Art
[0002] The preparation of polymer microporous foam materials by supercritical carbon dioxide foaming has the advantages of being green, environmentally friendly, non-toxic and pollution-free. At the same time, thermoplastic elastomer microporous foam materials have the advantages of being light, flexible, and having good resilience. Therefore, thermoplastic elastomer foams (TPU, TPEE, PEBA, etc.) are often used in the production of shoe materials. Compared with flexible gel and other materials, thermoplastic elastomer foam materials have better wear resistance and mechanical strength, which makes thermoplastic elastomer foam materials have a wider range of applications.
[0003] The nano-friction generator is a new energy source and sensor device based on friction electrification, which has received extensive research attention in recent years. The combination of the nano-friction generator and the thermoplastic elastomer microporous foam material has extremely far-reaching significance for the promotion and application of nano-generators and large-scale preparation.
[0004] So far, there are few cases of combining nano friction generators with supercritical foaming. At the same time, the few reports on combining nano friction generators with supercritical foaming mostly use the traditional nano generator configuration, that is, composed of a dielectric layer and a conductive layer. Such configurations often increase the process in the preparation, and the assembly of the dielectric layer and the conductive layer will also become a problem before application. Some other cases combine the fibrillation of engineering plastics with the microporous foaming of thermoplastic elastomers, but the fibrillation of engineering plastics will greatly increase the strength and stiffness of the thermoplastic elastomer foam material, making it difficult to use it in nano friction generators for wearable materials. Summary of the invention
[0005] In order to overcome the above defects of the prior art, the present invention provides a foam-based wearable single-layer friction nanogenerator and its preparation method and application.
[0006] The present invention provides a foam-based wearable single-layer friction nanogenerator, wherein the foam-based wearable single-layer friction nanogenerator integrates a dielectric layer and a conductive layer into one, and the electrical conductivity of the foam-based wearable single-layer friction nanogenerator is greater than 10 -7 S / m, dielectric constant greater than 400.
[0007] Compared with the prior art, the thermoplastic elastomer carbon material foam composite material prepared in the present invention has higher dielectric properties and certain electrical conductivity. The higher dielectric properties ensure that the thermoplastic elastomer foam material has higher polarization ability, thereby significantly improving the output performance of the nano friction generator. The certain electrical conductivity ensures that the prepared nano friction generator can integrate the dielectric layer and the conductive layer into one, so that no extra conductive layer is needed for conduction during use, thereby simplifying the structure of the nano generator. The electrical conductivity is greater than 10 -7 S / m.
[0008] The second object of the present invention is to provide a method for preparing a foam-based wearable single-layer friction nanogenerator, the preparation method specifically comprising the following steps:
[0009] S1, compounding a thermoplastic elastomer and a conductive carbon material in proportion to obtain a composite material;
[0010] S2, hot pressing the composite material obtained in step S1 through a flat vulcanizer to obtain a sample;
[0011] S3. Place the sample obtained in step S2 in an autoclave, introduce supercritical CO2 for supercritical foaming treatment, and then release the pressure for foaming to obtain a foam-based wearable single-layer friction nanogenerator.
[0012] Compared with the prior art, the present invention adopts the above preparation method, which has the following advantages: the conductive network formed by the conductive carbon material and the foaming structure work together to achieve a balance between the conductivity and dielectric properties of the material. A certain conductive network ensures the effective transmission of charge. At the same time, the introduction of conductive fillers brings a large amount of interfacial polarization, thereby significantly improving the dielectric properties of the material, thereby improving the triboelectric output performance of the material; the foaming treatment improves the flexibility and mechanical properties of the material. This is especially important for wearable devices, because these devices need to maintain stable performance in various dynamic environments.
[0013] In some embodiments, in step S1, the thermoplastic elastomer is selected from one of thermoplastic polyurethane, polyamide elastomer and polyolefin elastomer.
[0014] Specifically, different thermoplastic elastomers can be selected in different application fields. Due to its high elasticity and wear resistance, thermoplastic polyurethane can improve the durability and mechanical stability of the generator, and is suitable for wearable devices with frequent movement; the heat resistance and chemical resistance of polyamide elastomers enable them to perform well in applications under high temperature and complex environments, and are suitable for energy collection devices in industrial or special environments; the light weight and softness of polyolefin elastomers make them very suitable for wearable devices that directly contact the skin, thereby improving user comfort.
[0015] In some embodiments, in step S1, the conductive carbon material is selected from one of carbon nanotubes, carbon nanobeams, carbon nanofibers and graphene.
[0016] Specifically, different conductive carbon materials can be selected in different applications. Carbon nanotubes can improve the electrical output performance and mechanical stability of generators due to their high conductivity and mechanical strength, and are suitable for high-performance energy collection devices; the high aspect ratio and good dispersion of carbon nanobeams can improve the conductive network of composite materials and enhance the charge transfer efficiency, and are suitable for applications requiring high conductivity; the high surface area and good mechanical properties of carbon nanofibers can improve the conductivity and mechanical strength of composite materials, and are suitable for applications requiring comprehensive performance; graphene has extremely high conductivity and transparency, and graphene can improve the electrical output performance of generators while remaining light, thin and transparent, and is suitable for wearable devices and flexible electronic devices.
[0017] In some embodiments, in step S2, the compounding process is carried out in an internal mixer or an extruder, and the parameters of the internal mixer are as follows: processing temperature is 150-230°C, and rotation speed is 30-80rpm; the parameters of the extruder are as follows: temperature is 150-230°C, and rotation speed is 50-100rpm.
[0018] Compared with the prior art, the present invention adopts an internal mixer or an extruder for the composite processing process, wherein the internal mixer can ensure the uniform dispersion of the conductive carbon material in the thermoplastic elastomer matrix to form a continuous conductive network, thereby improving the conductivity and mechanical properties of the composite material, and is suitable for high-performance applications requiring high conductivity and mechanical strength; and the extruder is suitable for large-scale production due to its continuous production and high output characteristics, which can improve production efficiency and reduce costs, and is suitable for industrial-grade applications requiring large-scale production.
[0019] In some embodiments, in step S2, the parameters of hot pressing molding on a flat vulcanizing machine are as follows: pressure of 5-15 MPa, temperature of 180-200°C.
[0020] Compared with the prior art, the present invention adopts the above-mentioned hot pressing molding parameters, which have the following functions: appropriate high pressure can ensure that the composite material is fully compacted during the molding process, reduce internal voids and bubbles, and improve the density and uniformity of the material, while in the range of 180-200°C, the thermoplastic elastomer can be fully melted, ensuring that the material has good fluidity, which is conducive to filling the mold and forming a uniform structure. These advantages make the final prepared foam-based wearable single-layer friction nanogenerator have higher performance and wider application prospects, especially in the fields of wearable devices, portable power supplies and health monitoring systems.
[0021] In some embodiments, in step S3, the parameters of the supercritical foaming treatment are as follows: pressure of 8-30 MPa, foaming temperature of 70-130° C., saturation time of 0.5-2 h, and supercritical CO2 release rate of 5000-8000 ml / min.
[0022] Compared with the prior art, the present invention adopts the above parameters for supercritical foaming treatment, and its advantages are: appropriate pressure can control the solubility of supercritical CO2 in the material, thereby affecting the formation and growth of bubbles during the foaming process. Higher pressure can form smaller and more uniform bubbles, improving the pore size uniformity of the material; within the temperature range of 70-130°C, the thermoplastic elastomer can maintain good fluidity, which is conducive to the formation and growth of bubbles; the saturation time of 0.5-2h can ensure that the supercritical CO2 is fully dissolved in the material, and at the same time it will not be too long, thereby improving production efficiency; the release rate of 5000-8000ml / min can control the speed of the foaming process, avoiding uneven or ruptured bubbles caused by too fast or too slow.
[0023] The third object of the present invention is to provide a foam-based wearable single-layer friction nanogenerator for use in flexible touch switches, pressure monitoring or force monitoring.
[0024] The single-layer nano friction generator prepared by the present invention can directly rub against the ground, human body and other contactable objects. By connecting the nano generator with energy storage or monitoring equipment through a wire, charge transfer can be generated, thereby collecting energy. At the same time, the thermoplastic elastomer foam material has good flexibility and light weight, and is very suitable for use in wearable devices.
[0025] The fourth object of the present invention is to provide an application of a foam-based wearable single-layer friction nanogenerator in a shoe sole.
[0026] Specifically, the application includes integrating the foam-based wearable single-layer friction nanogenerator with the insole, connecting the foam-based wearable single-layer friction nanogenerator to the ADC module through a wire, and transmitting the voltage data to a mobile phone app through a single-chip microcomputer using Bluetooth to obtain a smart shoe material with step counting, plantar pressure monitoring and motion monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the current-time curve diagram of Example 4;
[0028] Figure 2 is the current-time curve diagram of Example 5;
[0029] Figure 3 is the current-time curve diagram of Example 6;
[0030] Figure 4 This is the current-time curve of Example 7. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0032] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0033] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer.
[0034] Comparative Example
[0035] The specific operation steps are as follows: hot press the thermoplastic polyurethane (TPU) at 200°C for 10 minutes through a flat vulcanizer, place the sample obtained by hot pressing in an autoclave and saturate it at 15MPa CO2 at 90°C for 60 minutes, then release the pressure and foam it. The multiplier of the foam material obtained is about 3 times, and the conductivity is about 10 -9 S / m, the dielectric constant is 13 at 40Hz, the peak-to-peak output voltage is 4V, the output current is 20nA, and the charge transfer is 5nC.
[0036] Example 1
[0037] This embodiment provides a method for preparing a foam-based wearable single-layer friction nanogenerator, and the specific operation steps are: thermoplastic polyurethane (TPU) and 1.5 parts of carbon nanotubes (CNS) are mixed in an internal mixer at 200°C and 50rpm for 10 minutes, and hot-pressed at 200°C for 10 minutes by a flat vulcanizer. The sample obtained by hot pressing is placed in an autoclave and saturated at 15MPa CO2 and 90°C for 60 minutes, and then the pressure is released for foaming. The ratio of the obtained foam material is about 3 times, and the conductivity is greater than 10 -3 S / m, the dielectric constant at 40Hz is 6163, the peak-to-peak value of the output voltage is 15V, the output current is 90nA, and the charge transfer capacity is 12nC. By improving the dielectric properties and conductive properties of the material, the triboelectric output performance of the material is significantly improved compared with the comparative example.
[0038] Example 2
[0039] This embodiment provides a method for preparing a foam-based wearable single-layer friction nanogenerator, and the specific operation steps are as follows: thermoplastic polyurethane (TPU) and 1 part of carbon nanobeam (CNS) are mixed in an internal mixer at 200°C and 50rpm for 10 minutes. The sample obtained by hot pressing is placed in an autoclave and saturated at 15MPa CO2 and 90°C for 60 minutes, and then the pressure is released for foaming. The ratio of the obtained foam material is about 3 times, and the conductivity is greater than 10 -3 S / m, the dielectric constant at 40Hz is 3572, the peak-to-peak value of the output voltage is 11.5V, the output current is 70nA, and the charge transfer capacity is 10nC. By improving the dielectric properties and conductive properties of the material, the triboelectric output performance of the material is significantly improved compared with the comparative example.
[0040] Example 3
[0041] This embodiment provides a method for preparing a foam-based wearable single-layer friction nanogenerator, and the specific operation steps are as follows: thermoplastic polyurethane (TPU) and 0.3 parts of carbon nanotubes (CNS) are mixed in an internal mixer at 200°C and 50rpm for 10 minutes. The sample obtained by hot pressing is placed in an autoclave and saturated at 15MPa CO2 and 90°C for 60 minutes, and then the pressure is released for foaming. The ratio of the obtained foam material is about 3 times, and the conductivity is greater than 10 -7 S / m, the dielectric constant at 40Hz is 438, the peak-to-peak value of the output voltage is 9.5V, the output current is 40nA, and the charge transfer capacity is 6nC. By improving the dielectric properties and conductive properties of the material, the triboelectric output performance of the material is significantly improved compared with the comparative example.
[0042] Example 4
[0043] This embodiment provides an application scenario of a foam-based wearable single-layer friction nanogenerator. The single-layer nanotriboelectric generator is connected to a monitoring device through a wire. The TPU foam nanotriboelectric generator prepared in Example 1 is pressed by hand, and the human body and the glove material rub against the TPU foam nanotriboelectric generator. The TPU foam nanotriboelectric generator can be used as a self-powered sensor to generate a corresponding current signal. This application can be used as a flexible touch switch, such as Figure 1 shown.
[0044] Example 5
[0045] This embodiment provides an application scenario of a foam-based wearable single-layer nano-friction generator. The single-layer nano-friction generator is connected to a monitoring device through a wire and integrated on a seat cushion. When the seat cushion is subjected to pressure, the seat cushion skin layer rubs against the single-layer nano-friction generator prepared in Example 1 to generate an output signal. Experiments were conducted on people of different weights, and it was found that the prepared single-layer nano-friction generator can monitor the pressure on the seat cushion, such as Figure 2 shown.
[0046] Example 6
[0047] This embodiment provides an application scenario of a foam-based wearable single-layer friction nanogenerator. The single-layer nanotriboelectric generator is connected to a monitoring device through a wire. The single-layer nanotriboelectric generator prepared in Example 1 is integrated on a boxing glove to monitor the strength of a punch. Figure 3 shown.
[0048] Example 7
[0049] This embodiment provides an application scenario of a foam-based wearable single-layer friction nanogenerator. The single-layer nanofriction generator prepared in Example 1 can be used for smart footwear. The nanofriction generator prepared in Example 1 is integrated with the insole. Since the nanofriction generator has good flexibility and wear resistance, it can ensure the service life without affecting the comfort. During walking, the single-layer nanofriction generator rubs against the ground to generate charge transfer. The nanofriction generator is connected to the ADC module through a wire, and the voltage data is transmitted to the mobile phone app through Bluetooth through the single-chip microcomputer to realize smart footwear with step counting, plantar pressure monitoring, and motion monitoring. Figure 4 shown.
[0050] From the above results, it can be seen that the thermoplastic elastomer carbon material foam composite material prepared by the present invention has high dielectric properties and high electrical conductivity. The high dielectric properties ensure that the thermoplastic elastomer foam material has high polarization ability, thereby significantly improving the output performance of the nano friction generator. The high electrical conductivity ensures that the prepared nano friction generator can integrate the dielectric layer and the conductive layer into one, so that no extra conductive layer is needed for electrical conduction during use. The electrical conductivity is greater than 10 -3 S / m.
[0051] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A foam-based wearable single-layer friction nanogenerator, characterized in that: The foam-based wearable single-layer friction nanogenerator integrates a dielectric layer and a conductive layer into one, and the conductivity of the foam-based wearable single-layer friction nanogenerator is greater than 10 -7 S / m, dielectric constant greater than 400.
2. A method for preparing a foam-based wearable single-layer friction nanogenerator as claimed in claim 1, characterized in that: The preparation method specifically comprises the following steps: S1, compounding a thermoplastic elastomer and a conductive carbon material in proportion to obtain a composite material; S2, hot pressing the composite material obtained in step S1 through a flat vulcanizer to obtain a sample; S3. Place the sample obtained in step S2 in an autoclave, introduce supercritical CO2 for supercritical foaming treatment, and then release the pressure for foaming to obtain a foam-based wearable single-layer friction nanogenerator.
3. The preparation method according to claim 2, characterized in that: In the step S1, the thermoplastic elastomer is selected from one of thermoplastic polyurethane, polyamide elastomer and polyolefin elastomer.
4. The preparation method according to claim 2, characterized in that: In the step S1, the conductive carbon material is selected from one of carbon nanotubes, carbon nanobeams, carbon nanofibers and graphene.
5. The preparation method according to claim 2, characterized in that: In step S2, the compounding treatment is carried out in an internal mixer or an extruder. The parameters of the internal mixer are as follows: processing temperature is 150-230°C and rotation speed is 30-80rpm; the parameters of the extruder are as follows: temperature is 150-230°C and rotation speed is 50-100rpm.
6. The preparation method according to claim 2, characterized in that: In step S2, the parameters of hot pressing molding on a flat vulcanizing machine are as follows: pressure is 5-15 MPa, and temperature is 180-200°C.
7. The preparation method according to claim 2, characterized in that: In step S3, the parameters of the supercritical foaming treatment are as follows: pressure is 8-30 MPa, foaming temperature is 70-130° C., saturation time is 0.5-2 h, and the rate of releasing supercritical CO2 is 5000-8000 ml / min.
8. An application of the foam-based wearable single-layer friction nanogenerator as claimed in claim 1 in flexible touch switches, pressure monitoring or force monitoring.
9. An application of the foam-based wearable single-layer friction nanogenerator as claimed in claim 1 in a shoe sole.
10. The use according to claim 9, characterized in that The application includes integrating the foam-based wearable single-layer friction nanogenerator with the insole, connecting the foam-based wearable single-layer friction nanogenerator with an ADC module through a wire, and transmitting voltage data to a mobile phone app through a single-chip microcomputer using Bluetooth to obtain a smart shoe material with step counting, plantar pressure monitoring and motion monitoring.